2015
DOI: 10.1109/led.2015.2432130
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Heterojunction Bipolar Transistor for Half-THz SiGe BiCMOS Technology

Abstract: The high-frequency performance of a novel SiGe HBT module with mono-crystalline base link is investigated in an industrial 0.13 µm BiCMOS environment. The main feature of this new HBT module is a significant reduction of the external base resistance as shown here by direct comparison with a conventional double-poly-silicon technology. Peak f T /f max values of 300 GHz/500 GHz are achieved. A minimum CML ring oscillator gate delay of 1.8 ps and a record operation frequency for a SiGe static frequency divider of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…5(a) for W E = 0.16 μm; for the reference transistor (L E = 5.69 μm), it is found that R Bi = 6.79 (24), 6.68 (25), and 6.76 (26); as a result, R Bx amounts to about 36 and is quite higher than R Bi .…”
Section: Impact Ionizationmentioning
confidence: 94%
See 4 more Smart Citations
“…5(a) for W E = 0.16 μm; for the reference transistor (L E = 5.69 μm), it is found that R Bi = 6.79 (24), 6.68 (25), and 6.76 (26); as a result, R Bx amounts to about 36 and is quite higher than R Bi .…”
Section: Impact Ionizationmentioning
confidence: 94%
“…This is the case for state-of-the-art SiGe:C HBTs, where the thermal resistances R TH have been pushed into the thousands of K/W [27], [29]- [31], and the openemitter breakdown voltage BV CBO has decreased down to 5-6 V and below [23], [24], [26], [27].…”
Section: B Proposed Improvementmentioning
confidence: 99%
See 3 more Smart Citations